Slots effect on CPW pentagonal patch antenna for 3.5 GHz 5G and 5.9 GHz DSRC applications - Ab Rashid, Amier Hafizun; Ahmad, Badrul Hisham; Hassan, Nornikman; Azemi, Saidatul Norlyana (2024)
This research investigates the effects of two different slots on the CPW pentagonal patch antenna for 5G and Dedicated short-range communications (DSRC). Initially, first antenna design, Antenna A is pentagonal patch antenna with pentagonal slots while the second antenna design B is constructed by a pentagonal patch antenna with mini multiple slots structure. This Antenna A performs best at 3.32 GHz and 5.77 GHz with - 20.83 dB and - 49.56 dB, respectively. Besised that, the Antenna B perfoms at 3.50 GHz and 5.92 GHz with - 46.13 dB and - 20.09 dB, respectively.